The Future of Cardiac Imaging: Innovations in MRI, CT, and Ultrasound Technologies - Faiz Ullah; Atiq Ur Rehman; Khan, Rahim Dil; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Cardiac imaging plays a crucial role in the diagnosis and management of cardiovascular diseases. Recent innovations in MRI, CT, and ultrasound technologies, particularly through the integration of artificial intelligence, are transforming clinical practice by improving image quality, reducing scan time, and enhancing diagnostic accuracy. Objective: To evaluate recent innovations in cardiac imaging technologies—specifically MRI, CT, and ultrasound—and explore their future potential for improving cardiovascular diagnosis and treatment. Materials and Method: A cross-sectional study was conducted at Department of Cardiology, Hayatabad Medical Complex Peshawar, Pakistan from August, 2024 to January, 2025. Data from 180 patients who underwent cardiac MRI, CT, or ultrasound were analyzed, with emphasis on advanced imaging technologies and their clinical impact. Results: Advanced techniques such as AI-enhanced MRI, photon-counting CT, and contrast-enhanced ultrasound significantly improved diagnostic performance. Multimodal imaging led to changes in clinical management in over 90% of cases. Conclusion: Emerging cardiac imaging technologies are reshaping cardiovascular diagnostics, offering enhanced accuracy and clinical utility across multiple modalities.